Global Citizenship Education (GCED) of Undergraduate Students by using Case-based Learning Technique to Promote Awareness of Respect for the Diversity of Refugees in Thailand - Woraurai, Suttipong; Kitipadung, Jitsupa; Boocha, Piya; Lamainil, Siwaporn; Nanposri, Natamon (Journal of Multidisciplinary in Humanities and Social Sciences, 2026)
This research article aimed to 1) compare the learning achievement of undergraduates in an experimental group who received case-based learning on refugee issues with a control group and 2) investigate the opinions of undergraduates regarding refugee issues in Thailand to develop global citizenship that respects diversity. A mixed-methods research approach was employed. The sample consisted of first-year undergraduates enrolled in the course "SWU 195 Creative Citizens for Society" during the second semester of 2022. The participants were divided into two groups: an experimental group of 80 students and a control group of 80 students, both selected through purposive sampling. Additionally, 17 students participated in focus group discussions. It was found that data analysis, using pre-test scores on refugee knowledge as a covariate to predict post-test achievement scores, revealed a significant difference in post-test achievement scores between the experimental and control groups (F=26.72, p < 0.05). After adjusting for the covariate's influence, the experimental group's learning achievement scores (mean = 16.86, SD = 0.50) were significantly higher than those of the control group (mean = 13.50, SD = 0.50). The results from the focus group discussions indicated that students in the experimental group demonstrated cognitive, affective, and behavioral characteristics consistent with being quality global citizens and achieving the expected learning outcomes.